Fundamentals of the Singapore property market. - Chien, Wei Wen. (2010)
The unique characteristic of Singapore’s property scene is portrayed by the coexistence of a dominant public sector and a smaller private sector. This paper attempts to examine the complex workings of the diverse factors that have given rise to the cycles of housing price fluctuations in the period between 1999 and 2008. A Two-Stage Least Squares analysis applied between the fundamentals of housing prices reveals that price expectations (illustrated by lagged housing prices) have significant explanatory effects on the fluctuations observed. Subsequently, rent-to-price ratio employed to assess the presence of speculative activity in the housing market concludes that price expectations effects are mainly reflecting changes in the timing homebuyers enter the property market. Empirical evidence also shows integration between both public and private housing markets, implying usefulness of information revealed in both markets, and the facilitation of household mobility in between housing markets.